0249 Sleeping In to Avoid Acting Out: The Association Between Sleep Regularity and Emotion Regulation. (25th May 2022) - Perez, Elliottnell; Sabet, Sahar; Soto, Pablo; Dzierzewski, Joseph
Abstract: Introduction: Sleep and emotions are closely intertwined facets of individuals' mental health and well-being. Previous studies have consistently shown that sleep is critical in the maintenance of emotion regulation; however, few research studies have examined the association between sleep regularity and emotion regulation skills. The current study seeks to answer this question by examining whether sleep regularity is associated with individual facets of emotion regulation, as well as overall emotion regulation ability. Methods: Secondary analysis was performed on data obtained from 999 individuals (M age=44.17, SD=16.23; 47.7% female) who participated in the Investigating Sleep Longitudinally Across Normal Development (ISLAND) online study. The Sleep Regularity Questionnaire was used to measure the degree to which individuals engage in consistent sleep behavior. The Difficulties in Emotion Regulation Scale was used to measure perceived overall emotion regulation ability, as well as individual facets of emotion regulation. Regression analyses were used to determine whether sleep regularity predicted difficulties in emotion regulation while controlling for age, race, gender, sleep quality, and total sleep time. Total sleep time and sleep quality information were obtained from item #4 and item #6 of the Pittsburgh Sleep Quality Index, respectively. Results: Less sleep regularity significantly predicted greater overall emotion regulation difficulties (p=.021, B=-.13). Less sleep regularity was associated with greater difficulty in individual facets of emotion regulation including emotional clarity (p<.001, B=-.05), impulse control (p<.001, B=-.05), nonacceptance of emotional responses (p=.009, B=-.04), and access to emotion regulation strategies (p<.001, B=-.06). Surprisingly, greater sleep regularity was associated with more difficulties with emotional awareness (p<.001, B=.09). Sleep regularity was not associated with difficulty engaging in goal-direct behavior (p=.103, B=-.02). Conclusion: Poorer sleep regularity significantly predicted greater overall emotion regulation difficulties. Findings from the current study add to the literature supporting the close links between sleep and emotion regulation, and suggest that the promotion and enhancement of consistent, regular sleep may be an important factor that leads to improved emotion regulatory skills beyond the sleep experience (i.e., sleep quality and duration). Additional research is needed to disentangle this association and identify additional factors or mechanisms that may further elucidate this association. Support (If Any): Research reported in this publication was supported by the National Institute on Aging of the National Institutes of Health under Award Number K23AG049955 (PI: Dzierzewski).